2020
DOI: 10.1097/prs.0000000000006483
|View full text |Cite
|
Sign up to set email alerts
|

Bone Tissue Engineering in the Growing Calvaria Using Dipyridamole-Coated, Three-Dimensionally–Printed Bioceramic Scaffolds: Construct Optimization and Effects on Cranial Suture Patency

Abstract: Background: Three-dimensionally-printed bioceramic scaffolds composed of β-tricalcium phosphate delivering the osteogenic agent dipyridamole can heal critically sized calvarial defects in skeletally mature translational models. However, this construct has yet to be applied to growing craniofacial models. In this study, the authors implanted three-dimensionally-printed bioceramic/ dipyridamole scaffolds in a growing calvaria animal model and evaluated bone growth as a function of geometric scaffold design and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
58
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(59 citation statements)
references
References 65 publications
1
58
0
Order By: Relevance
“…Skull injury repair has primarily been investigated in small animal models such as rats [26][27][28][29] and rabbits. [30][31][32] These studies have made important contributions to the development of strategies for calvarial bone regeneration. However, rodent calvaria are very different from that of humans, and a large animal CSD model is ultimately necessary for enabling clinical translation.…”
Section: Discussionmentioning
confidence: 99%
“…Skull injury repair has primarily been investigated in small animal models such as rats [26][27][28][29] and rabbits. [30][31][32] These studies have made important contributions to the development of strategies for calvarial bone regeneration. However, rodent calvaria are very different from that of humans, and a large animal CSD model is ultimately necessary for enabling clinical translation.…”
Section: Discussionmentioning
confidence: 99%
“…14 Bone regeneration is a popular research topic and numerous reports have been published on novel approaches to promote the best outcomes. [15][16][17] The investigation of such techniques in the craniofacial region has been reported clinically, but is still in its infancy due to the difficulty of developing a robust in vivo model of a craniofacial bone defect 18 (Figure 3).…”
Section: Craniofacial Bone Regenerationmentioning
confidence: 99%
“…These agents may enhance cellular recruitment and adhesion to the scaffold, promote proliferation then differentiation of specific cells important for bone regeneration and inhibit antagonistic activity (such as that of osteoclasts). [15][16][17][18]29,30 Calcium phosphates are widely used for bone reconstruction. 31,32 3D-printed β-tricalcium phosphate (β-TCP) scaffolds soaked in collagen and coated with dipyridamole have been investigated for bone regenerative purposes.…”
Section: Craniofacial Bone Regenerationmentioning
confidence: 99%
See 1 more Smart Citation
“…Another group developed a new 3D-printed β-tricalcium phosphate (β-TCP) scaffold loaded with the osteogenic agent dipyridamole and evaluated the effects of this implants to support bone growing within bilateral calvarial defects in rabbit [120]. After the implantation, the Authors observed a volumetrically significant osteogenic regeneration of calvarial defects, with a favorable preservation of suture patency, at least in the short term [120]. The same group then reproduced the experiments in an immature rabbit model, evidencing a comparable responsiveness with respect to autologous bone grafts.…”
Section: Tissue Engineering Strategiesmentioning
confidence: 99%